Educational level and the risk of depression after prostate cancer. (4th May 2019) - Friberg, Anne Sofie; Rask Moustsen, Ida; Benzon Larsen, Signe; Hartung, Tim; Wreford Andersen, Elisabeth; Halgren Olsen, Maja; Tjønneland, Anne; Kjaer, Susanne K.; Johansen, Christoffer; Brasso, Klaus; Oksbjerg Dalton, Susanne
Abstract: Background: The risk of depression is inversely associated with socioeconomic position in the general population; however, studies on the association in cancer populations are limited. The aim was to investigate if shorter education was associated with a higher risk of depression following prostate cancer diagnosis. Material and methods: This is a cohort study among participants in the Danish prospective Diet, Cancer and Health (DCH) study including 2337 men diagnosed with prostate cancer between 1997 and 2014. Primary outcome was indication of moderate to severe depression, defined as either a first hospital contact for depression or first use of antidepressants. The main indicator of socioeconomic position was education categorized into short (<9 years of education), medium (9–12 years) and long (>12 years). We retrieved information on education, depression and cohabitation status from Danish National Registries. Information on stage, primary treatment, lifestyle and anthropometry was obtained from medical records and questionnaires. Data were analyzed using Cox proportional hazards models adjusted for possible confounders and mediators. Results: The hazard of first depression was 1.86-fold higher (95% CI, 1.36–2.54) in prostate cancer patients with short education compared to those with long education. Adjustment for stage and primary treatment did not change the HRs, while adding comorbidity and lifestyle factors resulted in an HR of 1.65 (95% CI, 1.19–2.29). Men with medium education had a non-statistically significant 1.23-fold higher hazard of depression (95% CI, 0.95–1.59) than men with long education in the fully adjusted model. Educational differences were present in the cumulative incidence of first depression among cancer-free DCH study participants, but the level of first depression was substantially lower in this population than in prostate cancer patients. Conclusions: We found indication of social inequality in depression following prostate cancer. Patients and particularly men with short education might benefit from psychosocial intervention and support.